Fish-borne Parasitic Zoonoses in Turkish Waters - Solak,Kemal; Öktener,Ahmet; Yurdakul,Necati; Alaş,Ali (Gazi University Journal of Science, 2010)
The purpose of this study, to give information about zoonosis in freshwater and marine fishes. Three digeneans (Heterophyes heterophyes, Opisthorchis felinus, Centrocestus formosanus), one nematod (Anisakis simplex) and one cestod species (Diphyllobothrium sp.) which have zoonosis character were recorded from 15 host fishes. Anisakis was reported from marine fishes which is heavily consumed by people. Limited number of parasite having zoonosis character have been determined in marine and fresh water fishes in Turkey since 1931. For this reason, advanced studies are necessary about this subject.